Global research trends in gut microbiota and cellular senescence: a bibliometric and visual analysis from 2015 to 2025 - Huang, Shaoyang; Li, Jiangyan; Gu, Dandan; Li, Zhengliang; Chen, Hongyun; Xiong, Wei (Frontiers in Microbiology, 2025)
BackgroundThe human body’s intestinal microbiota is a vital “organ” that coexists with it and is intimately linked to both human health and illness. Human intestinal microbiota and its metabolites are a crucial component in the development of several diseases, according to an increasing number of studies that have started to examine the function of intestinal microbiota in various illnesses. Numerous recent studies have also shown a direct relationship between cellular senescence and the gut flora. The purpose of this study was to use bibliometric techniques to examine the themes and subjects of scholarly publications in this discipline during the past 10 or so years.MethodThe Web of Science Core Collection (WOSCC) database was searched for material published between 2015 and 2025. The study used VOSviewer and Citespace to explore the characteristics of this literature. Specific analyzes covered the number of publications, countries/regions studied, research institutions, authors, journals, citations, and keyword hotspots.ResultsThis study analyzed 2,911 publications on research related to gut microbiota and cellular senescence between 2015 and 2025, with a rapid increase in annual publications from 2020 onwards, peaking in 2024 (492 publications), with the United States and China dominating in terms of publications, and the University of Groningen demonstrating excellent academic influence in this field, with Chen, Wei, De Vos, Paul and Zhang, Hao being the three most influential authors in this field, Nature is the most influential journal in its field with 5,857 total citations, “Oxidative stress,” “Alzheimer’s disease” and “immunotherapy” are current hot topics of research.ConclusionResearch in the field of gut microbiota and cellular aging is growing rapidly. Current research focuses on gut microbiota and disease mechanisms (e.g., Alzheimer’s disease, immunotherapy, oxidative stress) and clinical translation, and interdisciplinary collaborations and technological innovations are expected to drive further development in this field. This bibliometric study provides a comprehensive analysis of the field and offers new ideas for future research.